KINERJA PEGAWAI BADAN PERTANAHAN NASIONAL KOTA PEKANBARU DALAM PELAYANAN ADMINISTRASI PENERBITAN SERTIFIKAT TANAH - Hakimi, Azyzy; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The performance of an organization is influenced by many factors, both within and outside of the individual including human resources, funds, materials, equipment, technology, and working mechanisms that take place within the organization. A conducive work environment or organizational culture will provide comfort so as to encourage the performance of employees, including how the condition of human relationships within the organization, both between superiors and subordinates. Administration Service of Land Certificate Issuance at the National Land Office of Pekanbaru City still has many complaints of the people who take care of the land certificate and the researcher wants to know how Performance of National Land Agency Official of Pekanbaru City in Administration Service of Land Certificate Issuance and what are the Factors inhibiting Performance of National Land Agency Pekanbaru City in Administration Service of Land Certificate Issuance. The concept of theory used is Employee Performance by Mitchel in Sedarmayanti which there are five indicators that are quality of work, timing, initiative, ability and communication. Researchers use qualitative descriptive method. And the theoretical concept of inhibiting factors used is mahsun which has a benchmark there are three that is the fastest service time and quality, the level of educational skills in accordance with field work and attendance or delay. In the data collecting researchers using observation, interview and documentation techniques. The results of this study indicate that the performance of National Land Agency Employee Pekanbaru In Service Administration Issuance of Land Certificate is not fully optimal and there are still many obstacles that occur. Then Factors inhibiting in the Performance of the National Land Agency Employee Pekanbaru in Service Administration of Land Certificate Issuance is the fastest service time and quality, the level of educational skills in accordance with field work. And the presence or delay Keywords: Employee Performance, Administrative Service